Answer:
b
Step-by-step explanation:
The equation:
3
x
2
−
5
x
−
12
=
0
is in the form:
a
x
2
+
b
x
+
c
=
0
with
a
=
3
,
b
=
−
5
,
c
=
−
12
The roots are given by the quadratic formula:
x
=
−
b
±
√
b
2
−
4
a
c
2
a
x
=
5
±
√
(
−
5
)
2
−
4
(
3
)
(
−
12
)
2
(
3
)
x
=
5
±
√
25
+
144
6
x
=
5
±
√
169
6
x
=
5
±
13
6
That is:
x
=
5
+
13
6
=
18
6
=
3
or
x
=
5
−
13
6
=
−
8
6
=
−
4
3
Answer:
4x + 10
Step-by-step explanation:
Answer:
(8 times 50)+ (8 times 2)
Step-by-step explanation:
Then put in some butter that will get you out
Answer:
72°
Step-by-step explanation:
tan x= PN/OP=95/31
⇒x ≈ 72°